2020
DOI: 10.1021/acsami.0c01846
|View full text |Cite
|
Sign up to set email alerts
|

Pyrene[4,5-d]imidazole-Based Derivatives with Hybridized Local and Charge-Transfer State for Highly Efficient Blue and White Organic Light-Emitting Diodes with Low Efficiency Roll-Off

Abstract: A family of pyrene­[4,5-d]­imidazole derivatives, PyPA, PyPPA, PyPPAC, and PyPAC, with different excited states are successfully developed. Among them, PyPPA and PyPPAC possess hybridized local and charge-transfer (HLCT) state, endowing them with pure blue fluorescence as well as high quantum yields. The nondoped organic light-emitting diode (OLED) based on PyPPA displays Commission Internationale de L’Eclairage coordinates of (0.14, 0.13) and achieves a maximum external quantum efficiency (EQE) of 8.47%, whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
58
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 87 publications
(59 citation statements)
references
References 65 publications
0
58
0
1
Order By: Relevance
“…Notably, the oscillator strength of the S 0 → S 1 is calculated to be as high as 2.4196, which is consistent with the value of 2.2082 derived from its relatively high molar extinction coefficients (log ε = 4.91 in dichloromethane). Such oscillator strength together with the radiative decay rate constant k r ≈ 5.6 × 10 8 s −1 in film are quite high levels in reported organic emitters, [35][36][37] indicating that high fluorescence efficiency for 2TPA-PPI can be anticipated. In contrast, the high-lying T 1 and T 2 states of 2TPA-PPI presented the LE states with the almost completely orbital overlap.…”
Section: Theoretical Calculationmentioning
confidence: 91%
“…Notably, the oscillator strength of the S 0 → S 1 is calculated to be as high as 2.4196, which is consistent with the value of 2.2082 derived from its relatively high molar extinction coefficients (log ε = 4.91 in dichloromethane). Such oscillator strength together with the radiative decay rate constant k r ≈ 5.6 × 10 8 s −1 in film are quite high levels in reported organic emitters, [35][36][37] indicating that high fluorescence efficiency for 2TPA-PPI can be anticipated. In contrast, the high-lying T 1 and T 2 states of 2TPA-PPI presented the LE states with the almost completely orbital overlap.…”
Section: Theoretical Calculationmentioning
confidence: 91%
“…with high η PL of 45% in the solid state which obtained a maximum η ext of 8.47% with CIE coordinates of (0.14, 0.13). 36 These previous studies have reported significant achievements in increasing the η PL of solid-state pyrene derivatives. Furthermore, η ext values exceeding 5%, which is the theoretical upper limit for traditional fluorescent OLEDs have been successfully attained using pyrene-based materials.…”
Section: Introductionmentioning
confidence: 98%
“…In recent years, materials with hybrid local and CT (HLCT) excited state were also well developed, which successfully achieved the merits of high η PL and a high output of singlet excitons in a series of donor (D)-acceptor (A) materials. 36,[41][42][43][44][45][46][47][48][49][50][51][52] HLCT materials also show the potential to maintain stable η ext at high brightness. Thus, there is still room for further enhancement of the η ext of blue OLEDs and low efficiency roll-offs in pyrene-based D-A system.…”
Section: Introductionmentioning
confidence: 99%
“…12,13 In comparison, the much short exciton lifetimes of HLCT emitters benefit to suppress exciton annihilation and thus improve efficiency roll-off. 14,15 Given the fact that the HLCT concept was proposed a few years ago, to date the development of HLCT emitters still lags behind TADF emitters. [16][17][18] In particular, device performances of most HLCT-based OLEDs remain restricted as their external quantum efficiencies (EQEs) are generally <10%, 10,15,[19][20][21][22][23] leaving much room for efficiency improvement.…”
Section: Introductionmentioning
confidence: 99%